Investigation of reagents with different chemical compositions for protection of oil primary refining equipment - Topilnytsky, Petro; Romanchuk, Victoria (Publishing House of Lviv Polytechnic National University, 2010)
The article deals with the investigation results of nitrogen-containing compounds solubility in non-polar and polar solvents, as well as low-temperature properties of formed solutions and their anticorrosive properties as corrosion inhibitors in the hydrocarbon-water two-phase system. Наведено результати дослідження розчинності азотвмісних речовин в полярних та неполярних розчинниках, низькотемпературні властивості отриманих розчинів та дослідження їх антикорозійних властивостей як інгібіторів корозії у двофазній системі вуглеводень-вода.
Дослідження реагентів різного хімічного складу для захисту нафтозаводського обладнання установок первинної переробки нафти
Keywords: corrosion; corrosion prevention; corrosion inhibitors; carbazolines; solvents; solubility; корозія; захист від корозії; інгібітори корозії; карбазоліни; розчинники; розчинність